Impact of exercise with blood flow restriction on muscle hypertrophy and performance outcomes in men and women. - Dawson Nancekievill; Ken Seaman; Danielle R Bouchard; Amy M Thomson; Martin Sénéchal (PLoS ONE)
Blood flow restriction training (BFRT) has been previously studied as an alternative form of resistance training to gain lean mass and improve performance outcomes. However, in all exercise studies of BFRT, the proportion of female participants represents only 17-29% of all research participants. This highlights a strong underrepresentation of females and the need for more knowledge on the impact of BFRT and sex differences. The primary objective was to compare the impact of 6-week BFRT on lean mass, strength, and performance outcomes between males and females. A total of 38 adults [age, 25.3 ±  3.1 years; female, n = 19 (50%)] performed whole-body resistance training program with blood flow restriction three times per week. Exercises were performed at 30% of 1-repetition maximum (1-RM) and blood flow restriction cuffs were set to 60% of each individual's limb occlusion pressure. Body composition was assessed via dual-energy x-ray absorptiometry and strength was measured using 1-RM. A significant increase in lean mass was observed in males (p = 0.009) and females (p = 0.023) with no difference in the change between groups (p = 0.279). Both males and females increased 1-RM for upper- and lower-body exercises, with significant interaction effects (time x sex) for chest press (p = 0.003), seated row (p = 0.038), knee flexion (p = 0.043), and knee extension (p = 0.035), suggesting males increased 1-RM more for these exercises. Furthermore, peak power was improved in males (p < 0.001) and females (p = 0.002) during a vertical squat jump, but a significant interaction (time x sex) effect was observed (p = 0.039), suggesting males increased to a greater extent. Males and females significantly increased lean body mass, to a similar degree, following six weeks of resistance training in combination with blood flow restriction. Likewise, both males and females improved muscle strength following 6-week BFRT, however males may improve strength to a greater extent than females.